PERFORMANCE ANALYSIS OF HEAT EXCHANGER AT PHOSPHATE ACID CONCENTRATED UNIT PT PETROCHEMICAL GRESIK - Erwan Adi Saputro; Widiya Ningrum; Muhammad Faishal Ma’arif; AR Yelvia Sunarti (Program Studi Teknik Mesin, Universitas Muhammadiyah Surakarta, 2022)
PT Petrokimia Gresik is the most complete fertilizer producing company and also produces fertilizer raw materials such as phosphoric acid. The process technology used in this company is Nissan C Process. One of the steps in this process is the phosphoric acid concentration unit. This unit consists of several steps such as evaporation, cooling, and fluorine scrubber. In the evaporation process, the most important equipment is the heat exchanger. As time goes by, it is necessary to evaluate the performance of this equipment. So, this case study aims to evaluate the performance of the heat exchanger, including the pressure of the heat exchanger the allowable pressure also to calculate the efficiency of the heat exchanger to determine whether the equipment is still suitable for use or not. Based on the calculation and analysis, obtained the pressure drop on the shell is 0.8817 psi, the pressure drop on the tube is 4.549 psi, and the efficiency of the equipment is 82.7%. So, it can be concluded that the heat exchanger used by PT Petrokimia Gresik is still suitable for use.